2017
DOI: 10.1037/pag0000148
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic adjustments of attentional control in healthy aging.

Abstract: In standard attentional control tasks, interference effects are reduced following incongruent trials compared to following congruent trials, a phenomenon known as the congruency sequence effect (CSE). Typical explanations of this effect suggest the CSE is due to changes in levels of control across adjacent trials. This interpretation has been questioned by the finding that older adults, individuals with impaired attentional control systems, have been shown to produce larger CSEs in the Stroop task compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
60
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(70 citation statements)
references
References 50 publications
9
60
1
Order By: Relevance
“…Based on previous findings (Ambrosi et al, 2016;Cragg, 2016;Iani et al, 2014) we expected to find the CSE in every age group. Furthermore, based on models of cognitive control development (Shulman et al, 2016) the CSE was predicted to increase in magnitude across the age groups, reflecting greater deployment of top-down control in response to changing task demands as a function of age, in line with previous studies that interpreted larger CSEs in the Simon and flanker tasks as reflecting better control modulation (e.g., Aschenbrenner & Balota, 2017). An alternative interpretation of CSE magnitude could be that a larger modulation actually means that there is less cognitive control deployed to tackle conflict in the first place, leading to incongruence impacting performance to a greater extent, therefore smaller CSEs might be an indicator of optimal performance.…”
Section: Irrespective Of the Exact Developmental Pattern In Behavioursupporting
confidence: 80%
See 3 more Smart Citations
“…Based on previous findings (Ambrosi et al, 2016;Cragg, 2016;Iani et al, 2014) we expected to find the CSE in every age group. Furthermore, based on models of cognitive control development (Shulman et al, 2016) the CSE was predicted to increase in magnitude across the age groups, reflecting greater deployment of top-down control in response to changing task demands as a function of age, in line with previous studies that interpreted larger CSEs in the Simon and flanker tasks as reflecting better control modulation (e.g., Aschenbrenner & Balota, 2017). An alternative interpretation of CSE magnitude could be that a larger modulation actually means that there is less cognitive control deployed to tackle conflict in the first place, leading to incongruence impacting performance to a greater extent, therefore smaller CSEs might be an indicator of optimal performance.…”
Section: Irrespective Of the Exact Developmental Pattern In Behavioursupporting
confidence: 80%
“…Therefore, it is important to control for the effects of stimulus repetitions and contingency learning if one wants to interpret the CSE in terms of control adjustments. Notably, recent studies have found the CSE pattern even after removing feature repetitions and target-distracter contingencies from the trial sequence, lending credence to the view that the CSE can occur in the absence of learning and memory confounds, presumably as a function of control adjustments (e.g., Aschenbrenner & Balota, 2017;Duthoo, Abrahamse, Braem, Boehler, & Notebaert, 2014b;Schmidt & Weissman, 2014;Weissman, Colter, Drake, & Morgan, 2015).…”
Section: Irrespective Of the Exact Developmental Pattern In Behaviourmentioning
confidence: 75%
See 2 more Smart Citations
“…This is consistent with previous findings that older participants exhibit significantly poorer performance in perceiving low-intensity happiness from older faces (e.g., [13]), but relatively intact performance on prototypical emotions displayed by younger adults [7][8][9]51]. Furthermore, it has recently been found that older adults are associated with larger congruency sequence effect [52,53] in the Stroop task compared to younger adult controls [54]. In future studies, it will be interesting to investigate the trial-to-trial carryover effect in emotion perception and to see how typical aging affects this interference effect.…”
Section: Age-related Behavioural Perceptual Performance Differencessupporting
confidence: 92%